The New Data on Distribution of Ixodic Ticks and Agents of Natural-Focal Infections Transferred by Them in Saratov Region - M. A. Turtseva (Проблемы особо опасных инфекций, 2009)
The expansion of areas and increase of the number of Ixodes ticks lead to distribution of ixodic tick-borne borreliosis agent in the territory of Saratov region. There exists the potential danger of activation of the natural foci of tularemia, formation of tick-borne encephalitis and Crimean hemorrhagic fever foci, their reservoirs and vectors being the ixodic ticks inhabiting the territory of the region.